Chirality-controlled preparation and single molecule characterisation of carbon nanotubes - Mashaghi Tabari, Samaneh (2011)
Nanostructures have gained increasing attention not only for their basic scientific richness, but also because they promise novelties and potentials that may lead to technological revolution. Carbon nanotubes (CNT’s) are one of the primary focuses of nanotechnology because of their unique physical properties such as huge Young modulus, high tensile strength, thermal and electrical conductivity. However many of their physical properties are extremely sensitive to their atomic structure. In order to optimize utilization of CNTs, their fundamental material properties should be well understood. A single shell of a CNT is composed of a wrapped up sheet of graphite. Depending on the wrapping, single wall carbon nanotubes (SWCNT) may have numerous different chiralities. Owing to SWCNT’s outstanding mechanical and electrical properties, many of their fundamental studies and technological applications require a population of tubes with identical chiralities. Separating SWCNT of different chiralities from each other is, however, a challenging problem. One proposed solution is to construct DNA-SWCNT hybrid and separate SWCNTs by their chiralities and diameter chromatographically. An oligomer of specific sequence of single-stranded DNA (ssDNA) has been shown to wrap around a SWCNT of a specific chirality and form ssDNA-SWCNT hybrid. Additionally self assembled DNA-SWCNT hybrids can be used a unique platform to study nucleic acid folding structures and other biophysical properties.